The Function of A2β-casein and Its Application Progress in Dairy Products - Yue QIU; Xingru LU; Yu SHEN; Jinfeng GUO; Yaping ZHENG; Xinyan YANG; Yujun JIANG; Chaoxin MAN (Shipin gongye ke-ji, 2023)
Milk is rich in many nutrients, including protein, lipids, carbohydrates, etc. Every 100 g of milk contains 3 g of protein, including mainly whey protein and casein. β-casein accounts for 24%~28% of total milk protein, and it mainly consists of two genotypes: A1 and A2. A1β-casein produces β-casein-7 after digestion, which can cause digestive disorders, cardiovascular diseases, and other adverse effects in humans. A2β-casein produces less or no β-casein-7 and has beneficial effects in gastrointestinal digestion, improving antioxidant function and lowering cholesterol concentration. This paper reviews the effects of β-casein genotypes after digestion in humans and discusses the probiotic functions of A2β-casein and its effects on human health. Moreover, the research progress of A2β-casein dairy products is described from the application of β-casein genotypes in dairy products to provide guidance for future research on the function of A2β-casein in dairy products.